2022
DOI: 10.3389/fpubh.2022.996036
|View full text |Cite
|
Sign up to set email alerts
|

Collectivism reduces objective mobility trends to public areas during the COVID-19 pandemic

Abstract: In order to slow down the spread of the coronavirus, staying at home and avoiding going outside have been either strongly recommended or stringently enforced by governments all over the globe. Previous studies found that people with more collectivist orientation were more willing to comply with governmental guidelines and engage in preventive behaviors such as social distancing. However, these studies were based on self-report data within a short period. The current study aims to overcome these limitations by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Notably, combining power values with collectivism yielded the construct of vertical collectivism ( Triandis, 1996 ). Further evidence indicates vertical collectivism is positively associated with conservation and self-enhancement values ( Clay et al, 2012 ; Soh & Leong, 2002 )—an orientation linked to greater COVID-19 concern and control intentions ( Biddlestone et al, 2020 ; Cho et al, 2022 ; Dang & Xiao, 2022 ; Germani et al, 2020 ; Huang et al, 2020 ; Lu et al, 2021 ). Vertical collectivism is proposed as an evolutionarily-developed disease-avoidance strategy ( Clay et al, 2012 ), suggesting conservation and self-enhancement values may function as infectious disease defenses ( Ackerman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, combining power values with collectivism yielded the construct of vertical collectivism ( Triandis, 1996 ). Further evidence indicates vertical collectivism is positively associated with conservation and self-enhancement values ( Clay et al, 2012 ; Soh & Leong, 2002 )—an orientation linked to greater COVID-19 concern and control intentions ( Biddlestone et al, 2020 ; Cho et al, 2022 ; Dang & Xiao, 2022 ; Germani et al, 2020 ; Huang et al, 2020 ; Lu et al, 2021 ). Vertical collectivism is proposed as an evolutionarily-developed disease-avoidance strategy ( Clay et al, 2012 ), suggesting conservation and self-enhancement values may function as infectious disease defenses ( Ackerman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, examining cultural values through this theoretical lens is essential for understanding the COVID-19 pandemic ( Ma, 2021 , 2022b ; Ma & Ye, 2021 ). Studies have shown collectivism values positively predict COVID-19 responses at individual and societal levels ( Biddlestone et al, 2020 ; Canatay et al, 2021 ; Cho et al, 2022 ; Dang & Xiao, 2022 ; Germani et al, 2020 ; Gokmen et al, 2021 ; Huang et al, 2020 ; Lu et al, 2021 ; Maaravi et al, 2021 ; Rajkumar, 2021 ; Webster et al, 2021 ). However, the broad, multifaceted nature of collectivism and individualism ( Talhelm & English, 2020 ) limits understanding of the specific relevance of cultural values to COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%